Giant Micelles of Organoplatinum(II) Gemini Amphiphiles - Maran, Umamageswaran (2008)
Organoplatinum(II) gemini amphiphiles with two different chain lengths are synthesized and characterized. Self-assembly at the air-water interface is investigated as a function of chain length and reduction in surface area by using Langmuir-trough techniques. The Langmuir-trough experiments lead to a conjecture that surface aggregates may be the adsorbing units. Atomic force microscopy on the transferred Langmuir-Schaefer films reveals spontaneous formation of wormlike micellar aggregates. A shear-induced transition and alignment are proposed for the observed effects.